2010
DOI: 10.1371/journal.pone.0015587
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sphingomyelin Synthase in Controlling the Antimicrobial Activity of Neutrophils against Cryptococcus neoformans

Abstract: The key host cellular pathway(s) necessary to control the infection caused by inhalation of the environmental fungal pathogen Cryptococcus neoformans are still largely unknown. Here we have identified that the sphingolipid pathway in neutrophils is required for them to exert their killing activity on the fungus. In particular, using both pharmacological and genetic approaches, we show that inhibition of sphingomyelin synthase (SMS) activity profoundly impairs the killing ability of neutrophils by preventing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…In vitro, neutrophils are able to kill Cn via an intracellular [6,7] or extracellular killing mechanism [8]. Both oxidative [6,9] and nonoxidative [10] killing of Cn by neutrophils have been described in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, neutrophils are able to kill Cn via an intracellular [6,7] or extracellular killing mechanism [8]. Both oxidative [6,9] and nonoxidative [10] killing of Cn by neutrophils have been described in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Class A genes (Table 3), upregulated primarily in normal PMN but not in CGD PMN, included dual-specificity phosphatase 16 (DUSP16) (increased 21-to 35-fold), which is acetylated by the Mycobacterium tuberculosis Eis protein, resulting in the suppression of certain host responses (37). Class C genes, altered primarily in CGD but not normal PMN, included several factors that might represent an attempt to control microbial growth, such as hepcidin (HAMP) (increased 3-fold), an antimicrobial peptide and hormone that decreases bioavailable iron in the circulation, and sphingomyelin synthase 2 (SGMS2) (increased 23-to 72-fold) which is important for PMN killing of Cryptococcus (38). It is unclear whether these differences reflect the continued survival of Granulibacter in CGD PMN and its killing by normal PMN or whether they reflect different host responses to Granulibacter.…”
Section: Resultsmentioning
confidence: 99%
“…We had previously observed that neutrophils obtained from immunocompetent mice having a fully functional immune system were able to kill C. neoformans (Qureshi et al, 2010). To this aim, we employed fresh murine neutrophils from TgΔ26 mice, and carried out the killing assay as described in the Section “Materials and Methods”.…”
Section: Resultsmentioning
confidence: 99%